Pass-through dos preços das commodities à inflação brasileira e a pandemia de Covid-19 - Costa, Leonardo Pereira da Silva (Universidade Federal de São Carlos, 2022)
The present study examines the pass-through of commodity prices to the Brazilian National Consumer Price Index (IPCA). The Covid-19 pandemic has once again raised concerns about inflation in Brazil and issues related to commodity price increases. Therefore, it is important to investigate to what extent commodity price increases impact inflation. Initially, a review of studies on exchange rate pass-through was conducted to provide an understanding of how the pass-through of commodities and exchange rates interacts to reach inflation. Next, existing studies on commodity price pass-through and the determinants identified by them were addressed. An econometric study was then conducted using the Vector Autoregressive (VAR) methodology, which allows us to evaluate the impact of shocks between various variables. The results indicate the existence of commodity price pass-through to inflation even in the presence of exchange rate appreciation, meaning that shocks in commodity prices are passed on to domestic prices in the first few months, peaking in the second month. Additionally, it was found that between the third and seventh periods, the pass-through declines rapidly compared to later periods. Finally, the impulse-response function of the nominal exchange rate to inflation was not statistically significant.
Pass-through of commodity prices to Brazilian inflation and the Covid-19 pandemic
Keywords: Pass-Through; Câmbio; Commodities; Inflação; Pandemia; VAR; CIENCIAS SOCIAIS APLICADAS::ECONOMIA